2001
DOI: 10.1149/1.1354612
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Carbon Starting Material on Carbon Fluoride Synthesized at Room Temperature: Characterization and Electrochemistry

Abstract: International audienceA series of carbon fluorine compounds (CxF) was prepared by catalyzed, room-temperature reactions of natural graphite, petroleum coke, and coal-tar-pitch coke with fluorine in the presence of HF and IF5. Elemental analysis indicated that most of the compounds had carbon-to-fluorine ratios between 1 and 2. X-ray diffraction, X-ray photoelectron spectroscopy, and infrared spectroscopy suggest that carbon-fluorine bond strengths were intermediate between ionic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…This is believed to be related to the amount and type of impurities present in the material used as a binder for these kinds of electrodes, e.g., coal-tar pitch in TT amorphous carbon (Figure 3). This is consistent with the findings by Root et al (13) who found that pure coal-tar pitch was poorly fluorinated even by direct chemical fluorination using gaseous F 2 at elevated temperatures. Thus, the coal-tar pitch may confer a beneficial effect of helping the carbon material resist the formation of stable carbonfluorine (C-F) bonds.…”
Section: Electrochemical Behavioursupporting
confidence: 93%
“…This is believed to be related to the amount and type of impurities present in the material used as a binder for these kinds of electrodes, e.g., coal-tar pitch in TT amorphous carbon (Figure 3). This is consistent with the findings by Root et al (13) who found that pure coal-tar pitch was poorly fluorinated even by direct chemical fluorination using gaseous F 2 at elevated temperatures. Thus, the coal-tar pitch may confer a beneficial effect of helping the carbon material resist the formation of stable carbonfluorine (C-F) bonds.…”
Section: Electrochemical Behavioursupporting
confidence: 93%
“…The voltage initially drops and then increases steadily to reach the main voltage plateau after few minutes; such a behavior has been already observed for graphite fluorides. [4,5] The average potential is stable during the discharge in agreement with the unique C-F bonding (determined by 13 C and 19 F solid state NMR), which is still covalent whatever the fluorination conditions. The most unexpected observation is that the experimental capacity (Qexp) significantly exceeds the theoretical value (Qtheo), for those two materials.…”
Section: Resultssupporting
confidence: 64%
“…For the pristine electrode, the peaks at 284.3 and 291.8 eV in C 1s spectrum correspond to C-C and C-F in CF x , respectively, while the peak at 287.6 eV is assigned to C-F in PVDF. In F 1s spectrum, the peaks at 688.6 and 686.8 eV can be assigned to C-F in CF x and Fe-F in FeF 3 , respectively [15]. The relative intensity ratio of the first to the second peak is about 1.25:1.…”
Section: Resultsmentioning
confidence: 91%